Estudo do comportamento doentio na sepse experimental e o envolvimento da disfunção cerebral e ativação microglial - Goldim, Mariana Pereira de Souza (2018)
Introduction: Behavioral and physiological alterations occur due inflammatory process, called as sickness behavior. Sepsis is an overwhelmed systemic inflammation response due an infection, leading to organ damage, including brain, causing neurological alterations and cognitive brain damage. Objective: Investigate sickness behavior and its involvement with neuroinflammation and cognitive damage in experimental sepsis. Methods: Male Wistar rats of two months of age were submitted to sepsis model of cecal ligation and puncture (CLP group) or laparotomy only (sham group). Sickness behavior were evaluated prior surgery, 6h, 12h and 24h after, for analysis of acute neuroinflammation and blood-brain barrier (BBB) leakage at brain structures: amygdala, nucleus accumbens, hippocampus and prefrontal cortex at 24h after CLP. Or daily evaluations during eight days for analysis of long term neuroinflammation and cognitive damage. Sickness behavior were determined by the following criteria: hypothermia, anorexia, adipsia, anhedonia and lethargy. The sickness behavior score (SBS) were determined by the alteration of healthy behavior prior sepsis. Also, were evaluated the involvement of microglia activation, by inhibition of M1 microglia by minocycline. Results: CLP animals showed increased sickness behavior in acute and chronic evaluation. It was observed an association of SBS and BBB leakage, IL-6 cytokine, corticosterone, BDNF, nitrite/nitrate levels and neuroinflammation in amygdala. Chronic SBS was associated with long term cognitive damage. Microglial activation showed to be involved with SBS, neuroinflammation and cognitive damage. Conclusion: Physiological alterations of sickness behavior are associated with inflammation markers and damage to CNS. Being this protocol of behavioral evaluation help the analysis of CNS alterations and pathways involved in sepsis.